2008
DOI: 10.1017/s1751731107001486
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tannic acid application on alfalfa hay: in vitro rumen fermentation, serum metabolites and nitrogen balance in sheep

Abstract: Alfalfa protein is poorly utilised by ruminants due to its rapid degradation in rumen. The objective of the study was to assess the influence of spraying tannic acid (TA) on chopped alfalfa hay on in vitro rumen fermentation and nitrogen (N) retention by sheep. Alfalfa hay with and without TA was fed to sheep to determine nutrient digestibility and N balance. TA was sprayed on chopped alfalfa at three concentrations to determine its effect on in vitro fermentation of dry matter (DM) and N balance in sheep. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
(62 reference statements)
3
8
0
Order By: Relevance
“…DM and NDF apparent digestibilities were not affected by the experimental diets. These results are consistent with some previous studies (Getachew et al 2008a). In contrast to our findings, Zimmer and Cordesse (1996) observed that DM, OM and NDF digestibilities were decreased by hydrolysable tannins.…”
Section: Intake Apparent Digestibility and N Balancesupporting
confidence: 93%
See 1 more Smart Citation
“…DM and NDF apparent digestibilities were not affected by the experimental diets. These results are consistent with some previous studies (Getachew et al 2008a). In contrast to our findings, Zimmer and Cordesse (1996) observed that DM, OM and NDF digestibilities were decreased by hydrolysable tannins.…”
Section: Intake Apparent Digestibility and N Balancesupporting
confidence: 93%
“…DM, OM and N intake were similar across treatments. Similar results were observed by others (Vahmani and Naserian 2006;Getachew et al 2008a;Gholizadeh et al 2010). Gholizadeh et al (2009) reported that replacement of PB for beet pulp decreased DM intake in Baloochi sheep.…”
Section: Intake Apparent Digestibility and N Balancesupporting
confidence: 92%
“…Conversely, the high urinary N excretion for lucerne (S0) results from the higher digestible N content and the higher ruminal N degradability of lucerne compared with sainfoin (quadratic contrast, Figure 3). Getachew et al (2008a) observed higher faecal N as the tannic acid level on lucerne hay was increased. Tiemann et al (2008) studied the effect of using two tannin-rich shrub legume species as replacements for a herbaceous high-quality legume (Vigna unguiculata) on the nutritive value of a diet composed of tropical grasses (Brachiaria brizantha and V. unguiculata).…”
Section: N Utilisationmentioning
confidence: 81%
“…Lower NDF translates into both increased DMI and milk yield within a forage family [3]. Regarding alfalfa protein, approximately 80% is degraded in the rumen of polygastric animals, but addition of tannins to alfalfa feed decreases rumen protein degradability and increases protein absorption [30].…”
Section: Forage Qualitymentioning
confidence: 99%